A comparative analysis of the cytotoxicity of cyanotoxins using in vitro (cell culture) and in vivo (mouse) assays - Naicker, D. (University of Pretoria, 2013)
Dissertation (MSc (Paraclinical Studies))--University of Pretoria, 2007.